The evaluative legitimacy of social entrepreneurship in capitalist welfare systems - Ewald Kibler; Virva Salmivaara; Pekka Stenholm; Siri Terjesen (Elsevier, 2022)
Social entrepreneurs start ventures to tackle social problems, and these ventures have the potential to outperform other social service providers in welfare states. We leverage theories of legitimacy and Varieties of Capitalism to examine national experts’ (N = 361) assessments of the efficiency of social enterprises relative to state and civil society. Our multilevel analysis across 11 welfare states shows that social enterprises are perceived as a more efficient solution to social problems when a liberal or socialist logic dominates a given state’s market coordination and social welfare provision. However, when institutional logics are in conflict, the assigned legitimacy of social entrepreneurship is diminished.